Reactions to COVID-19 Media Awareness Campaigns: Insights from Gweru Urban High Density Suburbs - Beauty Muromo; Francis Muromo (Journal of Linguistics and Communication Studies, 2024)
This study explored the public’s reaction to COVID-19 awareness campaigns against a myriad of conspiracies towards the COVID-19 vaccines. These conspiracies are peddled in both the mainstream and social media platforms. It is this study’s contention that some awareness messages were very convincing culminating in some sections of the public being vaccinated while on the other hand the messages were misconstrued leading to some sections of the public also rejecting to be vaccinated. In a quest to unravel the myths behind the conspiracies, this study through a mixed methods approach, interrogated 500 residents of Senga and Nehosho suburbs of Gweru of their opinions by Facebook and WhatsApp platforms. These platforms were used to avoid the spread of the pandemic through physical contact. Findings from the study indicated that the media played a crucial role in informing the public of the COVID-19 pandemic, culminating in some people getting vaccinated while on the other hand, some rightly rejected the vaccines. Those who got vaccinated indicated that the awareness messages were quite informative and thus convinced them to seek projection. On the other hand, those who rejected the vaccines did so due to ignorance, fear of the unknown, religious and political orientation among other reasons. The study therefore recommends that media messages be packaged with education so as to fully equip audiences with proper information in order for them to make informed decisions.